Emotion and magnitude perception: number and length bisection - DROIT-VOLET, SYLVIE (Frontiers in Neurorobotics, 2013)
Studies of the effect of emotional stimuli on time perception have shown that a threatening stimulus produces a temporal lengthening effect compared to a non-threatening stimulus. In order to better understand the mechanisms underlying this emotion-related time distortion, the present study examined distortions in the judgment of other quantities - number and length - under the same emotional conditions as those previously used for time. However, the nature of the presentation of quantities was manipulated by using a sequential and a non-sequential presentation. The participants were thus given a number or a length bisection task in a sequential or a non-sequential modality of stimulus presentation. In each condition, the participants completed trials in which the probe stimulus was followed by either an aversive stimulus or a non-aversive stimulus. The results showed that the quantities were judged longer, with the set of dots judged bigger and the line judged longer, on the trials which contained aversive stimulus, but only when these quantities were presented sequentially. In comparison with the time distortions obtained in time bisection, these distortions in the bisection judgment of sequentially presented quantities suggests that emotion affected the dynamic process of accumulation of units in working memory.